Dynamics of Students' Learning Motivation in the Process of Learning English in Higher Education - Maba, Wayan (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2023)
The key element influencing learning activity is motivation. Learning objectives are difficult to attain without having high motivation to learn. Students that are motivated will be more engaged in their learning, which will push them to understand and use English properly. This research uses a descriptive method to examine students' learning motivation in learning English. This research is a survey by distributing questionnaires, and then the questionnaire results will be analyzed quantitatively and descriptively qualitatively. This research found that students already have good attitudes and interest in learning English, but there is still a need for development to achieve optimal English learning outcomes. Students still often feel afraid to communicate in English because they fear making mistakes in pronunciation, grammar, and using the correct language. This research implies that university lecturers should continually motivate their students to communicate in English and facilitate students with a positive and conducive learning environment.